Perjanjian Pra-Nikah Perspektif Islam: Studi Fenomenologi di Era Society 5.0 - Aa Sofyan (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2023)
This article examines the urgency of prenuptial agreements in the context of Society 5.0, characterized by digital transformation and technological integration. Prenuptial agreements are seen as an important instrument for regulating marital relationships fairly and transparently, in line with modern values such as gender equality and justice. In the Society 5.0 era, prenuptial agreements can be utilized efficiently and easily accessed. The study also identifies the potential negative impacts of prenuptial agreements, including power imbalances between partners, reduced fairness in the division of joint assets, difficulties in revoking agreements, potential tension in marital relationships, and negative impacts on children, highlighting the need for a balance between the benefits and risks of prenuptial agreements in the context of an increasingly complex and diverse modern society. This research employs a qualitative approach with data analysis involving literature reviews and case studies. The findings of this article suggest that prenuptial agreements in the Society 5.0 era can serve as a basis for wiser policies in regulating marital relationships in the future.